Potential of Moringa oleifera Seeds as a Natural Coagulant for Turbidity and LAS Removal from Detergent Wastewater - Arfan, Aulia Rhamdani; Irawati, Utami; Indah, Rahma; Hikmah, Nawwal (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Detergent wastewater contains high levels of surfactants, particularly Linear Alkylbenzene Sulfonate (LAS), which are persistent and harmful to aquatic ecosystems. This study evaluated the potential of Moringa oleifera seed extract (MOS) as a natural coagulant for detergent wastewater, compared with alum as a synthetic coagulant. The coagulation process was carried out using the jar test method at varying dosages (100–1500 mg/L) and pH levels (4–9). Turbidity was measured following SNI 06-6989.25-2005, while LAS concentration was analysed using the Methylene Blue Active Substances (MBAS) method. Results showed that MOS achieved optimum performance at 1500 mg/L and pH 4, with a turbidity removal efficiency of 94.96% (final turbidity 4.76 NTU) and LAS removal efficiency of 88.94% (final concentration 0.58 mg/L). In comparison, alum reached its optimum at 200 mg/L and pH 6, with lower LAS removal efficiency. Validation with wastewater samples stored for 1–3 nights indicated that MOS maintained consistent performance, while alum showed fluctuating results. An in-silico docking study further confirmed the molecular interaction between LAS and MOS proteins, with a binding energy of –4.8 kcal/mol, supporting the observed experimental results. These findings demonstrate that MOS is a promising, low-cost, and environmentally friendly alternative to alum for detergent wastewater treatment.